Penguatan Kapasitas Media Lokal: Strategi Dhoho TV dalam Menghadapi Tantangan Digitalisasi - Moh. Izharil Ulul ‘Azmi; Zakariya Anshor, Muhammad; Sinta Kusuma Wardani; Novi Rizikiyani; Lukman Hakim; Dony Rano Virdaus (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
The development of digital technology has brought major changes to the television industry. Television media, both conventional and local, face challenges to adapt to digitalization in order to remain relevant and competitive. With the advent of internet technology, television now has to compete with streaming platforms and social media, which make it easy to access information anytime and anywhere. The aim of this research is to determine Dhoho TV's mass communication strategy in maintaining its existence in the digital era. This research uses a descriptive qualitative approach with a case study method. Data was obtained through interviews, observation and documentation. The results obtained in this research are that there are 2 strategies used by Dhoho TV. The first strategy is to maintain program programs that are in great demand by the public, namely the